Analisis Pengaruh Temperatur Bahan Bakar terhadap Daya Keluaran GT 1.2 pada Beban Maksimal di PLTGU Blok 1 PT Nusantara Power UP Muara Karang - Muhammad Fadly Purwanto; Muhammad Ridwan (Universitas Muhammadiyah Metro, 2026)
Efficiency enhancement in Combined Cycle Power Plants (CCPP) is a crucial factor for reducing operational costs and optimizing energy production. One of the key parameters influencing the performance of a gas turbine is the fuel temperature at the combustor inlet. This research aims to quantitatively analyze the effect of fuel temperature variations on the power output, specific fuel consumption (SFC), and thermal efficiency of the GT 1.2 gas turbine. The analysis was conducted using operational data from the Block 1 CCPP of PT Nusantara Power UP Muara Karang under maximum load conditions, with fuel temperature varied from 22°C to 300°C, and validated using Cycle-Tempo software simulation. The results indicate that pre-heating the fuel consistently improves the gas turbine's performance. It was found that the thermal efficiency increased from 32,25 % to 33,19 %, while the specific fuel consumption (SFC) was successfully reduced from 388.21 gr/kWh to 376.65 gr/kWh. It is concluded that fuel pre-heating is a proven and effective strategy for enhancing efficiency and optimizing gas turbine operations in a CCPP.